Cyberterrorism definition patterns and mitigation strategies: A literature review - SEissa, Israa G.; Ibrahim, Jamaludin; Yahaya, Nor-Zaiasron (International Journal of Science and Research (IJSR), 2017)
This paper aim to contribute to the body of knowledge on cyber terrorism, improves awareness of cyber terrorism definition, boundaries, potential targets, crime patterns and effective mitigation strategies through analysis of relevant literature on the issue produced in recent years. It details the definitional origins of the concept and It looks at motivational factors and level of destruction necessary to classify a cyber-attack as cyberterrorism. The second sections is devoted to literature distinguishing cyberterrorism from hacking and cybercrime. Section three details the stages of a cyber attack, Section four lists the types of infrastructure targeted for cyber terrorists and Section five focuses on mitigation strategies.